Body Weight, Insulin Resistance, and Inflammatory Biomarkers in Rats Fed Normal-Fat, High-Fat, and Ketogenic Diets Supplemented with Vitamin D - Al-Badarein, Bushra Omar; Ahmad, Mousa Numan (Jordan Journal of Agricultural Sciences, 2021)
Ketogenic (KD) and high-fat (HFD) diets and vitamin D (VD) produce variable effects on insulin secretion and body weight (BW), but mechanisms remain unclear. We investigated the effects of normal fat diets (NFD), KD, and HFD with and without VD on BW and serum glucose, insulin, VD, insulin resistance, C-reactive protein, interleukin-6, and tumor necrosis factor-alpha in rats. Three isocaloric NFD, KD, and HFD containing respectively protein-carbohydrate-fat (NFD: 14.8%-75.7%-9.5%; KD:20.2%-10.3%-69.5%; HFD:15.2%-42.7-42.0%) and three other similar diets but with (1000 IU/kg) VD were used. Forty-five adult male Sprague-Dawley rats were used, 5 rats were sacrificed at the start, remainders were randomly divided into NFD (n=15) and HFD (n=25), and fed for 8 weeks, then 5 rats from each were sacrificed. NFD remainders were divided into 2 subgroups (n=5) and fed NFD and NFD-VD, and HFD remainders were divided into 4 subgroups (n=5) and fed HFD, HFD-VD, KD, and KD-VD for further 8 weeks, then all rats were sacrificed. BW and food intake were measured, food conversion ratio (FCR) was calculated, and biological variables were determined following standard protocols. BW change and FCR (-15.6± -10.13g; 0.033±0.350 respectively) of rats fed KD-VD were the lowest (P<0.05) compared to those fed KD (144.8±1.47g; 0.189±0.050), HFD-VD (143.0±8.49g; 0.187±0.100), HFD (155.8±0.3g; 0.203±0.010), NFD-VD (142.8±6.34g; 0.183±0.009), and NFD (51.0±1.02g; 0.074±0.110) respectively. BW change correlated (P<0.01) with food intake (r=0.752), % carbohydrate (r=0.292), and % fat (r=0.341). None of the diets affected other biomarkers. Results clearly show BW-reducing effects for KD-VD that may be mediated by changes in food intake and dietary fat and carbohydrate proportion.